1991
DOI: 10.1007/bf02751131
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry for syndromology

Abstract: In diagnosing certain syndromes, abnormal facial features such as hypertelorism, low set ears or wide nasolabial distance are taken into consideration. Most often the description is from a visual impression, which may prove wrong as it is only relative. Detailed studies have, so far been only from the west, except for two, from northern India. These values may not suit us as facial features and measurements vary in different populations. This study was undertaken to set up a standard for the south Indian popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 2 publications
6
24
1
Order By: Relevance
“…Between early adulthood (16–25 years) and old age (41–67 years), the FIPD had increased by 2.2 mm and 1.3 mm (Viktorin’s and PD-5, respectively), with the NIPD increasing by 2.8 mm and 2.3 mm (Viktorin’s and PD-5, respectively). This indicates that in line with previous reports,6,9,38–41 the increase in FIPD and NIPD in early adulthood continues towards an individual’s late 30s, and begins to decrease in the fourth decade of life.…”
Section: Discussionsupporting
confidence: 91%
“…Between early adulthood (16–25 years) and old age (41–67 years), the FIPD had increased by 2.2 mm and 1.3 mm (Viktorin’s and PD-5, respectively), with the NIPD increasing by 2.8 mm and 2.3 mm (Viktorin’s and PD-5, respectively). This indicates that in line with previous reports,6,9,38–41 the increase in FIPD and NIPD in early adulthood continues towards an individual’s late 30s, and begins to decrease in the fourth decade of life.…”
Section: Discussionsupporting
confidence: 91%
“…Outer canthal measurements of studies from Wales and United States were similar to our results (24). Two studies from India determined longer outer canthal length than in our study (16,25). In the study of Feingold and Bossert, which is accepted as standard in the measurement of the external canthal, the 50th percentile value of the outer canthal distance was determined as 6.32 cm in term infants, as in our study (1).…”
Section: Discussionsupporting
confidence: 87%
“…Jones et al (11) suggested that PFL related closely to eye size, a neural organ, and PFL indirectly reflects neural growth. When compared with the Indians and the Nigerians, the palpebral fissure of the HKC seems to be more medially oriented (2, 22).…”
Section: Discussionmentioning
confidence: 99%